Interventions to promote healthy lifestyle behaviors in children and adolescents in summer day camps: a scoping review - David Larose; Melvin Chih-Shing Chen; Shirin Panahi; Jennifer Yessis; Angelo Tremblay; Vicky Drapeau (BMC, 2023)
Abstract Background Children and adolescents have suboptimal physical activity and eating habits during summer breaks. Unlike the school setting, there is little evidence on interventions to promote healthy lifestyle behaviors in Summer Day Camps (SDCs). Methods The aim of this scoping review was to examine physical activity, healthy eating, and sedentary behavior interventions in the SDCs. A systematic search on four platforms (EBSCOhost, MEDLINE, EMBASE, and Web of Science) was performed in May 2021 and was updated in June 2022. Studies related to promoting healthy behaviors, physical activity, sedentary behaviors and/or healthy eating among campers aged 6 to 16 in Summer Day Camps were retained. The protocol and writing of the scoping review were done according to the guidelines of the "Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR)". Results Most interventions had a positive effect on the behavioral determinants or the behaviors themselves (i.e., physical activity, sedentary behaviors, or healthy eating). Involving counsellors and parents, setting camp goals, gardening, and education are all relevant strategies in promoting healthy lifestyle behaviors in SDCs. Conclusions Since only one intervention directly targeted sedentary behaviors, it should strongly be considered for inclusion in future studies. In addition, more long-term and experimental studies are needed to establish cause-and-effect relationships between healthy behavior interventions in SDCs and behaviors of children and young adolescents.